2022
DOI: 10.1155/2022/8809708
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Value of Echocardiography Combined with Serum h-FABP and cTnI in Myocardial Infarction and Its Evaluation Value in Left Ventricular Function

Abstract: Objective. To explore the value of color Doppler echocardiography (CDE) combined with serum heart-type fatty acid-binding protein (h-FABP) and cardiac troponin I (cTnI) in the diagnosis of myocardial infarction and its evaluation value in left ventricular function. Methods. A total of 44 patients with myocardial infarction who were treated in Cangzhou Central Hospital from October 2018 to February 2020 were included in the observation group, and 45 healthy subjects were included in the control group. The serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Therefore, we developed a thermal effect model by extending the irradiation time in this study. In terms of index selection, we selected the changes in the levels of myocardial enzymes (CK-MB and HBDH) [ 8 ] and myocardial injury markers (H-FABP, cTnT, and NT-pro BNP) [ 9 , 10 ]. The reason behind our selection is that they are not only more closely related to clinical manifestations but are also more sensitive to myocardial injury than traditional myocardial enzymes such as AST.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we developed a thermal effect model by extending the irradiation time in this study. In terms of index selection, we selected the changes in the levels of myocardial enzymes (CK-MB and HBDH) [ 8 ] and myocardial injury markers (H-FABP, cTnT, and NT-pro BNP) [ 9 , 10 ]. The reason behind our selection is that they are not only more closely related to clinical manifestations but are also more sensitive to myocardial injury than traditional myocardial enzymes such as AST.…”
Section: Introductionmentioning
confidence: 99%
“…The heart index also supported our results, demonstrating that both pea peptides and the two-peptide composite can reduce hypertensive heart disease, and the effect of the two-peptide composite is more obvious. However, there are other biomarkers for cardiomyocyte injury and heart function, such as heart-type fatty acid binding protein (HFABP) and left ventricular ejection fraction (LVEF) [ 51 , 52 ]. Therefore, further study could be needed to explore the two-peptide composite’s effect on heart function.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%